2022
DOI: 10.3389/fphys.2022.843473
|View full text |Cite
|
Sign up to set email alerts
|

Application of a multicomponent model of convectional reaction-diffusion to description of glucose gradients in a neurovascular unit

Abstract: A supply of glucose to a nervous tissue is fulfilled by a cerebrovascular network, and further diffusion is known to occur at both an arteriolar and a microvascular level. Despite a direct relation, a blood flow dynamic and reaction-diffusion of metabolites are usually considered separately in the mathematical models. In the present study they are coupled in a multiphysical approach which allows to evaluate the effects of capillary blood flow changes on near-vessels nutrient concentration gradients evidently. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
0
2
0
7
Order By: Relevance
“…Therefore, to avoid this risk, one needs to consider right processes with right localization. In particular, for H/H I.2.2 models of glucose distribution in a neurovascular unit it was shown that the geometry of inner flux dysconnectivity barrier essentially determines the reply of the system on changes of cerebral blood flow in the capillary [10,11]. The same effect of geometrical polymorphism appears in other system corresponding to H/H I.2.1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid this risk, one needs to consider right processes with right localization. In particular, for H/H I.2.2 models of glucose distribution in a neurovascular unit it was shown that the geometry of inner flux dysconnectivity barrier essentially determines the reply of the system on changes of cerebral blood flow in the capillary [10,11]. The same effect of geometrical polymorphism appears in other system corresponding to H/H I.2.1.…”
Section: Discussionmentioning
confidence: 99%
“…При этом процесс синтеза PLP является АТР-зависимым, что, в свою очередь, требует энергетических затрат и активации митохондриального окислительного фосфорилирования в нейронах и астроцитах. Увеличение содержания PLP, активирующее глициндегидрогеназу, которая является частью системы расщепления глицина, что приведет к его снижению в плазме и спинномозговой жидкости и, возможно, повлияет на микроциркуляцию [37] и снабжение нервной ткани ключевыми метаболитами, в частности глюкозой [38,39].…”
Section: дефицит витамина вunclassified
“…Примечательно, что глицин оказывает прямое действие на дилатацию артериол Том 10, Выпуск 5, 2022 [50,51], что является важнейшим аспектом общего воздействия данной аминокислоты на состояние ЦНС [52]. Воздействие на систему кровотока в микрососудах и капиллярах приводит к теоретически обоснованному [53][54][55] и экспериментально подтвержденному увеличению содержания глюкозы в тканях [56].…”
Section: иные сопутствующие и метаболические эффекты глицинаunclassified